Hubungan antara Job Demands dengan Kepuasan Kerja pada Perawat PPPK di RSUP Dr. M. Djamil Padang - Awfe, Qaulan Sadida; Rinaldi, Rinaldi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop a comprehensive analysis of competitive strategies for the food and beverage business at Kios La Galigo, with a particular focus on increasing sales turnover amid the growing and intense competition in Makassar City. The research was conducted on the Small and Medium Industry (IKM) of Kios La Galigo, located in Makassar, using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis approach to identify and formulate alternative strategic options that the company can apply to strengthen its market position. Through the SWOT analysis, the study identified internal strengths and weaknesses, as well as external opportunities and threats that affect the company’s competitiveness. As a result, seven alternative strategies were developed, offering various approaches that Kios La Galigo could consider to improve its business performance and sustain growth in a challenging market environment. To determine which strategies would be the most effective, the Quantitative Strategic Planning Matrix (QSPM) was used to prioritize and evaluate the attractiveness of each alternative. Based on this analysis, two main strategies were selected as the most suitable for implementation. The first recommended strategy is to maintain and improve the quality of both products and customer service, which is essential for customer satisfaction and loyalty. The second strategy is to expand partnerships with distributors, aiming to increase market reach and strengthen the company’s distribution network for better operational efficiency.